Highly porous niobium oxide/carbon matrix materials with distinct pseudocapacitive performances in aqueous electrolytes. (1st March 2021) - Dai, Yang; Ma, Lipeng; Hu, Jiaqi; Wang, Jianghong; Yan, Hao; Zhang, Huaiyu; Wang, Hui-Qiong; Lai, Chunyan; Li, Wenrong; Zheng, Jin-Cheng
Highlights: NbO2 /porous carbon composite material is prepared by a sugar blowing method. Possess unique porous and intergrowth structure. As the electrode active material for high performance supercapacitor. 184 Fg −1 (484 F cm −3 ) at 1 A g −1 and 130 Fg −1 (342 F cm −3 ) at 50 A g −1 . Symmetric supercapacitor delivers maximum 18.2 Wh kg −1 and 81000 W kg −1 . Abstract: NbO2 /porous carbon matrix composite material for supercapacitor application is prepared by a facile sugar blowing method. Owing to the unique porous and intergrowth structure, this material possesses effective electron-ion-conductive-network. Thus, it delivers an impressive capacitance of 261 Fg −1 (686 F cm-3) at 1 A g −1 and 175 Fg −1 (460 F cm −3 ) at 50 A g −1 in 1 M H2 SO4 . With a wide potential window of 1.8 V in 1 M Li2 SO4, it achieves 184 Fg −1 (484 F cm −3 ) at 1 A g −1 and 130 Fg −1 (342 F cm −3 ) at 50 A g −1, respectively. Remarkably, a symmetric two-electrode-cell with this material using 1 M Li2 SO4 retains its operating voltage of 1.8 V, delivering 18.2 Wh kg −1 (47.9 Wh l −1 ) at 810 W kg −1 (2130.3 W l −1 ), and 10.5 Wh kg −1 (27.6 Wh l −1 ) at 81000 W kg −1 (213030 W l −1 ), as well as excellent cyclic capability (>10000 cycles). These interesting performance reveals the significant prospect of this material to be utilized in supercapacitors and other electrochemical devices.